1962
DOI: 10.1104/pp.37.3.342
|View full text |Cite
|
Sign up to set email alerts
|

Invertase in Cell Walls of Plant Tissue Cultures

Abstract: In 1955 Ball (1) published a report in which he demonstrated that the growth of various tissue cultures upon media containing certain oligosaccharides resulted in the appearance of the hydrolysis products of these sugars in the medium. Ball speculated that the appearance of these hydrolysis products was due to the uptake of the oligosaccharide, hydrolysis within the tissue cells, and a subsequent release of the smaller molecules into the medium. Epp (8)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1967
1967
1990
1990

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 19 publications
(12 reference statements)
0
18
0
Order By: Relevance
“…Invertase I activity continues to rise during incubation preceding the period of greatest growth (i.e., cell elongation), and it then declines. In the absence of exogenous substrate and hormone, cell division activity within the excised intercalary meristem rapidly declines (12 (15), in contrast to other tissues where the bulk invertase activity is associated with the cell wall fraction (6,16,28). Invertase activity could not be removed from the cell wall fraction by the procedures tested.…”
Section: Methodsmentioning
confidence: 83%
“…Invertase I activity continues to rise during incubation preceding the period of greatest growth (i.e., cell elongation), and it then declines. In the absence of exogenous substrate and hormone, cell division activity within the excised intercalary meristem rapidly declines (12 (15), in contrast to other tissues where the bulk invertase activity is associated with the cell wall fraction (6,16,28). Invertase activity could not be removed from the cell wall fraction by the procedures tested.…”
Section: Methodsmentioning
confidence: 83%
“…Invertase activity has been reported to be present in the soluble and insoluble (cell wall) fractiotis (Straus, 1962;Straus & Campbell, 1963;Copping & Street, 1971;Krishnan, Blanchette & Okita, 1985). Our preliminary studies showed that the orchid invertase was also present in the cell wall fraction.…”
Section: Discussionmentioning
confidence: 99%
“…In tbe orcbid culture medium containing sucrose as tbe sole carbon source, tbere was an increase in glucose concentration witb a concomitant decrease in total carbohydrate, niie same bad been reported for some otber plant tissues in culture, and invertase activity was implicated (Straus, 1962;Straus & Campbell, 1963;Coppling & Street, 1972;Thorpe & Meier, 1973). To date, tbere is no report of invertase activity in orchid tissue culture under culture conditions.…”
Section: N T K O D L' C T [ O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of the activities of sucrose-degrading enzymes in plant tissue cultures (3,14,15), for example, vary in the degree of, correspondence observed between enzyme activity and growth rate. Growth rate may be limited by substrate concentration as well as by enzyme concentration, and a simple correspondence between enzyme activity and growth is unlikely to exist throughout a culture period during which the carbohydrate supply in the medium may become completely exhausted (16).…”
Section: Sucrosementioning
confidence: 99%